2013
DOI: 10.1007/s00405-013-2486-0
|View full text |Cite
|
Sign up to set email alerts
|

Otomycosis in the north of Iran: common pathogens and resistance to antifungal agents

Abstract: Otomycosis as a kind of external otitis can be caused by various species of fungi. To use the appropriate treatment, it is necessary to identify the causal agent of otomycosis. The aim of this study was to determine the pathogens that caused otomycosis and also the efficacy of different antifungal agents. 100 patients with diagnosis of otomycosis/otitis extern were entered in this study. Bacterial culture was performed by eosin methylene blue agar, blood agar; and Sabouraud dextrose agar was used to culture th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 15 publications
4
33
1
1
Order By: Relevance
“…However, in some investigations, treatment failure (9-17%) has been reported. is failure can be due to the type of drug chosen, disregarding the possibility of resistance of the organism causing this disease, not completing the therapeutic course [27,37,38], genetic variations, surgery, or use of hearing assistive technology systems [10,11,29,30]. As an important finding of the present study, of the 161 individuals with otomycosis, only 3.1% of them had relapse after completing the therapeutic course and stated complete improvement of the disease by ENT and the patient satisfaction with their treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in some investigations, treatment failure (9-17%) has been reported. is failure can be due to the type of drug chosen, disregarding the possibility of resistance of the organism causing this disease, not completing the therapeutic course [27,37,38], genetic variations, surgery, or use of hearing assistive technology systems [10,11,29,30]. As an important finding of the present study, of the 161 individuals with otomycosis, only 3.1% of them had relapse after completing the therapeutic course and stated complete improvement of the disease by ENT and the patient satisfaction with their treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Otomycosis is one of the relatively common diseases in the world including Iran, claiming around 30% of ear infections [1][2][3][4][5][6][7]. Among the contributing and stimulating factors for development of otomycosis are manipulating the ears, humidity, heat, age, predisposing primary bacterial infection, and immune system disorders [8][9][10][11][12]. e main clinical findings of otomycosis include pruritus, scaling, discharge, and pain [9,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered to be opportunistic occurring after treatment of bacterial infection and develops unilaterally in healthy persons and in many times a pride posing problem is present [6][7][8]. It has been found that otitis externa (OE) constitutes about 5-20% of ear consultations to otorhinolaryngologists; the majority of these cases are caused by bacteria and in 9-25% fungal agents are the cause and the microorganisms which attribute for these clinical conditions are present as saprobes in nature [9][10][11]. Otomycosis can be presented with non-specific manifestations such as itching, discomfort and otalgia, aural fullness, tinnitus decrease in hearing and otorrhea [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It is generally considered to be opportunistic occurring after treatment of bacterial infection and develops unilaterally in healthy persons and in many times a pride posing problem is present [6][7][8]. It has been found that otitis externa (OE) constitutes about 5-20% of ear consultations to otorhinolaryngologists; the majority of these cases are caused by bacteria and in 9-25% fungal agents are the cause and the microorganisms which attribute for these clinical conditions are present as saprobes in nature [9][10][11]. Otomycosis can be presented with non-specific manifestations such as itching, discomfort and otalgia, aural fullness, tinnitus decrease in hearing and otorrhea [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%